Extremeness Aversion and Choice Set Composition: Exposure to Multiple Extreme Options Reduces Extremeness Aversion - Sharif, Marissa A; Webb, Elizabeth C; Bhatia, Sudeep (Journal of Consumer Research, 2026)
Abstract Extremeness aversion—the tendency for consumers to prefer middling options in a choice set—is an incredibly robust and well-studied phenomenon. However, it has primarily been studied in the context of two- or three-option choice sets. In six studies (Ntotal = 9,377), we suggest that consumers’ aversion to extreme options depends on the frequency of similar options in the choice set. In particular, we find that consumers are relatively more likely to choose an option that is in an extreme relative position when they are exposed to multiple extreme options, an effect not predicted by standard theories of context-dependent choice. This occurs because consumers perceive objectively extreme (vs. intermediate) options as relatively more typical of the product category. We demonstrate that this effect is robust across different types of compositions, hypothetical and incentive-compatible studies, and in a variety of decision contexts (e.g., purchasing an item vs. choosing an activity to complete). Furthermore, we identify boundary conditions, such as the type of occasion consumers are choosing for.